Misja Ramakriszny jako nowy ruch religijny - Rogacz, Dawid (My University, 2013)
The aim of my paper is to show that the Ramakrishna Mission is a new religious movement, not just a neohinduist sect, commonly classified as Neo-Vedanta. I will refer to the administrative structure and profile of the Mission and to the teaching of the patrons of the movement: Sri Ramakrishna Paramahansa (1836–1886) and his most important disciple, Swami Vivekananda (1863–1902). Their teaching opens the movement (and the Hindu tradition) to the West through the concept of religious pluralism.
Keywords: Ramakrishna; Neo-Vedanta; Hinduism